ANALISIS DISKRIMINAN FLEKSIBEL FLEXIBLE DISCRIMINANT ANALYSIS - , RASITA NINGRUM, Herni Utami., S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flexible discriminant analysis is development of linear discriminant analysis, which is used to solve the problem of classification on non-parametric regression. Flexible discriminant analysis replaces parametric regression with non-parametric regression, one of the non-parametric regression can be used is Multivariate Adaptive Regression Splines (MARS). MARS aims to predict, the best MARS models which is have minimum of Generalized Cross Validation (GCV). The assumptions is used in flexible discriminant analysis modeling is that there is no outlier data, homogeneity variance-covariance matrix. In case study, classify dissolved oxygen levels of water based on 5 predictor variables.